Competitive performance of elite track-and-field athletes: Variability and smallest worthwhile enhancements - Hopkins, W. G. (Sportscience, 2005)
PURPOSE: To describe the reproducibility of competitive performance of elite track-and-field athletes and to derive the smallest worthwhile enhancements of performance in these events. METHODS: The data were official results of events in 17 competitions of an annual series of the International Amateur Athletic Federation extending over 101 d. Typical within-athlete variability from competition to competition was derived as a coefficient of variation by re-peated-measures analysis of log-transformed times (for running and hurdling events) or distances (for jumping and throwing events). The smallest worth-while performance enhancement was taken as half the within-athlete variability. RESULTS and DISCUSSION: Within-athlete variabilities were as follows: run-ning and hurdling events up to 1500 m, 1.0%; longer runs and steeplechase, 1.4%; triple and high jump, 1.7%; pole vault and long jump, 2.4%; discus, javelin, and shot put, 2.8% (90% confidence limits all ~×/÷1.13). The differences between events presumably reflect differing contributions of energy systems, pacing strategies, wind resistance and skill. Females may have had a little more variability in performance (~1.1×) than males in some events, possibly because of less depth of competition. There was some evidence that variability increased with increasing time between competitions for the short running events (from ~0.7% for ~1 wk to ~1.1% for ~100 d). The top-half athletes in each event were less variable than the bottom-half in running and hurdling up to 1500 m (0.8 vs 1.1%) and in longer runs and steeplechase (1.1 vs 1.6%), but differences were unclear in the other events. A likely explanation is less consis-tent motivation in endurance athletes who were not in the medal stakes. CONCLUSIONS: Coaches and sport scientists should focus on enhancements of as little as 0.3-0.5% for elite track athletes through 0.9-1.5% for elite field athletes.